GENERATION Z'S BEHAVIOR IN INVESTING : UNIQUE AND ODD - Tamtomo, Agatha Pricillia Sekar; Setiawan, Doddy; Budiono, Graceilla Kristia Seraphim; Ulfa, Mutia (Magister Manajemen of Universitas Islam Nahdlatul Ulama Jepara, 2024)
This study was conducted with the aim of determining the influence of investor behavioral factors on risk perception and investment decisions in generation Z stock investors. These behavioral factors consist of overconfidence and emotion and use financial literacy as a moderator. The respondents in this study were 361 generation Z investors in Indonesia. Sampling used purposive sampling technique, while data analysis used SEM (Structural Equation Modeling) method using smartPLS software. The results of this study indicate that overconfidence and emotion influence the risk perception of generation Z investors. Financial literacy has also been shown to moderate the relationship between overconfidence and investment decisions. Unlike other similar studies, financial literacy was found to be a very strong driving factor in influencing the existence of the relationship between overconfidence and investment decisions. One of the reasons is the rapid development of technology and the differences in the hierarchy of needs in this generation. This study can help brokerage and securities companies to plan in dealing with young investors, especially generation Z, to better direct and introduce risks in stock investors.